Regulation and Application of the Doctrine of Res Ipsa Loquitur in the Settlement of Consumer Disputes in Indonesia - Suryamah, Aam; Yuanitasari, Deviana; Angela, Irene Maria; Assalihee, Muhammadafeefee (Journal of Law and Legal Reform, 2024)
Consumer disputes may be resolved by non-litigation or litigation, with the latter being reserved for extreme cases. Companies are obligated to pay customers' compensation claims. The parties to a dispute should not be unfairly treated when the burden of evidence is not evenly distributed. In order to avoid an unfair burden of evidence mistakes that hurt other parties, the burden of proof has to be examined case by case. Law No. 8 of 1999 on Consumer Protection specifies the burden of evidence in Article 28. When it comes to enforcing the law in Indonesia, doctrines are accepted sources of law from outside the country. An interesting topic for debate is the regulation and use of the res ipsa loquitur doctrine in consumer dispute resolution in Indonesia. This method has a normative legal bent. The Consumer Protection Law does not explicitly govern the res ipsa loquitur notion, even though it is acknowledged in Indonesian consumer dispute settlement. Applying res ipsa loquitur to consumer disputes may help ensure fairness, which is in line with the Consumer Protection Law's established reverse burden of proof.